Cell-nonautonomous local and systemic responses to cell arrest enable long-bone catch-up growth in developing mice. - Alberto Roselló-Díez; Linda Madisen; Sébastien Bastide; Hongkui Zeng; Alexandra L Joyner (PLoS Biology)
Catch-up growth after insults to growing organs is paramount to achieving robust body proportions. In fly larvae, injury to individual tissues is followed by local and systemic compensatory mechanisms that allow the damaged tissue to regain normal proportions with other tissues. In vertebrates, local catch-up growth has been described after transient reduction of bone growth, but the underlying cellular responses are controversial. We developed an approach to study catch-up growth in foetal mice in which mosaic expression of the cell cycle suppressor p21 is induced in the cartilage cells (chondrocytes) that drive long-bone elongation. By specifically targeting p21 expression to left hindlimb chondrocytes, the right limb serves as an internal control. Unexpectedly, left-right limb symmetry remained normal, revealing deployment of compensatory mechanisms. Above a certain threshold of insult, an orchestrated response was triggered involving local enhancement of bone growth and systemic growth reduction that ensured that body proportions were maintained. The local response entailed hyperproliferation of spared left limb chondrocytes that was associated with reduced chondrocyte density. The systemic effect involved impaired placental function and IGF signalling, revealing bone-placenta communication. Therefore, vertebrates, like invertebrates, can mount coordinated local and systemic responses to developmental insults that ensure that normal body proportions are maintained.